Flight activity of aphids as potential vectors of viral infection of alfalfa in Serbia - Jovičić, Ivana S; Radonjić, Andja; Petrović-Obradović, Olivera (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2017)
Flight activity of aphids as potential vectors of viral infection of alfalfa plants were monitored in Serbia for the first time in Europe. Research was conducted at the location Progar (Srem) for two years using six yellow water traps. A total of 1626 individual winged aphids were collected. The collected specimens were classified into 49 different taxa. During the two-year study, maximum population density of aphids and maximum potential vector activity were noted at the beginning of June, during the second alfalfa intercut. More than 65% of the collected specimens were potential vectors of the most important alfalfa viruses, Alfalfa mosaic virus (AMV) and Cucumber mosaic virus (CMV). The most numerous winged aphid species on alfalfa were Aphis craccivora, Aphis fabae, Aphis gossypii, Aphis pomi/spiraecola and Therioaphis trifolii. The Morisita-Horn similarity index was used to calculate similarities in species composition among the traps. High values of this index showed no significant differences among the aphids in traps. It indicates that one trap alone could provide good insight into the abundance, aphid diversity and number of potential vector species in small alfalfa fields.
Keywords: Aphididae; Vectors; Plant viruses; Alfalfa